Effect of HUVECs on proliferation and stemness of hDPSCs silencing integrin α6 - AN Qi, ZHANG Weiwei, HE Lina, LI Yanping, PAN Shuang, NIU Yumei (Kouqiang yixue)
Objective To investigate the effect of human umbilical vein endothelial cells (HUVECs) on the proliferation and stemness of human dental pulp stem cells (hDPSCs) silencing with integrin α6 (ITGA6). Methods ITGA6 silencing lentivirus was used to interfere the ITGA6 expression of hDPSCs, and its silencing efficiency was detected. Then HUVECs were added to the chambers to co-culture, and the experiments were divided into four groups (sh-NC, sh-ITGA6, sh-NC+HUVECs and sh-ITGA6+HUVECs). hDPSCs in the sh-NC and sh-ITGA6 groups were transfected with sh-NC and sh-ITGA6 respectively. hDPSCs transfected with sh-NC and sh-ITGA6 were co-cultured with HUVECs in the sh-NC+HUVECs group and sh-ITGA6+HUVECs group respectively. The proliferation capacity of hDPSCs of each group was examined by CCK-8 and EdU on day 7. Immunofluorescence detected the expression of Stro-1, and Real-time PCR was used to detect the expression of Oct4 and Nanog. Results ①Fluorescence microscopy showed that the transfection efficiency was about 80%. Real-time PCR and Western blot results showed that sh-ITGA6 lentivirus effectively interfered with ITGA6 expression in hDPSCs. ②CCK-8 results showed that on day 5 of co-culture, the proliferation ability of the sh-ITGA6+HUVECs group was superior to that of the sh-ITGA6 group (P<0.05); on day 7, the proliferation ability of the sh-NC+HUVECs and sh-ITGA6+HUVECs group was superior to that of the sh-NC and sh-ITGA6 group (P<0.05). EdU results showed that the DNA synthesis ability of hDPSCs in the co-culture group was significantly stronger than that in the single-culture group (P<0.05). ③Immunofluorescence staining revealed that the expression of Stro-1 in the co-culture group was significantly stronger than that in the single-culture group. ④Real-time PCR results showed that the expression of Oct4 in the co-culture group was higher than that in the single-culture group (P<0.05); the expression of Nanog in hDPSCs with sh-ITGA6 was elevated by the addition of HUVECs co-culture (P<0.05). Conclusion HUVECs significantly enhance the proliferation and stemness of hDPSCs silencing integrin α6.